Intellectual Production in Socialist Europe 1956-1968 : Ideas in Flux - Blagojević, Una; Borisova, Natalia; Konarzewska, Aleksandra (Literature and Cultural Studies E-Books Online, Collection 2026., 2025)
Between the Thaw and the Prague Spring, Socialist Europe experienced a brief yet intense period of intellectual ferment. Intellectual Production in Socialist Europe 1956-1968 explores the shifting landscape of literature, philosophy, literary theory, and political thought in the wake of Stalinism and on the cusp of postmodernism. Bridging cultural analysis and intellectual history, this volume offers fresh insights into a period that shaped Socialist Europe for decades.